The provenance and tectonic settings of the greywacke member of the late neoproterozoic hazara formation lesser himalayas, northern pakistan: Evidence from geochemistry and petrography - Dar, Qamar Uz Zaman; Renhai, Pu; Sajid, Zulqarnain; Mehmood, Mubashir; Abdul, Wahab (Penerbit Universiti Kebangsaan Malaysia, 2021)
The petrographic and geochemical analysis of the greywacke horizon of the late Neoproterozoic Hazara Formation from the Hazara Mountains has been investigated to determine the provenance, tectonic settings and weathering history of the sediments. The Late Neoproterozoic Hazara Formation is a thick sedimentary sequence comprising of greywacke, shale, argillites, siltstone, and limestone. The greywackes are characterized by fine to medium-grained, moderately sorted and sub-angular to sub-rounded framework grains. They are rich in quartz, lithic fragments and clay minerals. The petrographic investigation of the greywackes categorized them as feldspathic greywacke in the QFR diagram. The quartz content is higher in sandstone and may reach to 70%, which indicates a weathered felsic source. Chemical Index of Alteration values of greywacke suggests that the source region has experienced highly weathering conditions with a warm and moist climate. Various geochemical interpretations, elemental ratios like Th/Sc, La/Sc,Th/Cr, and positive Eu anomalies indicate that the greywackes of the Hazara formation derived from a felsic source and were deposited within an active continental margin tectonic settings. The main source area of the sediments of the greywackes was located to south to southeast, which may possibly be the Aravali orogeny, central Indian craton and Bundelkhand craton. Finally, the geochemical data of the major elements point to a felsic igneous provenance for the greywacke.